Screening of Anti-Quorum Sensing Activity from Selected Chinese Herbs Against Chromobacterium violaceum (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Overuse of antibiotics was contributed to the increasing of bacterial infection resistance against antibiotics and caused a serious issue to the public health. Anti-quorum sensing is a new alternative ways or treatments to fight bacterial pathogenicity. Traditional Chinese herbs were screened of their anti-quorum sensing activities. Six selected traditional Chinese herbs were screened for a simple anti-quorum sensing activity by using Chromobacterium violaceum as the biomonitor. Two out of these herbs were found to be able to exhibit anti-quorum sensing properties; Lycium barbarum and Zingiber officinale. Extraction from Lycium barbarum has stronger anti-quorum sensing activity than Zingiber officinale. Colonies of biomonitor C. violaceum treated with Lycium barbarum almost fully loss its purple pigment. The loss and lack of purple colour from the colonies of C. violaceum indicated that quorum sensing activity was inhibited by the herb’s extracted. It is believed that this herb contains rich source of compounds to fight or control pathogenic bacteria and potentially a new therapeutic way to reduce the development of antibiotic resistanc
Keywords: Chromobacterium violaceum; Anti-quorum sensing; Quorum Sensing; Chinese herbs; Antibiotic resistance